Oxytocin receptor gene (OXTR) polymorphisms and social, emotional and behavioral functioning in children and adolescents: A systematic narrative review. (April 2022) - Kohlhoff, Jane; Cibralic, Sara; Hawes, David J; Eapen, Valsamma
Abstract: This study systematically reviewed available evidence regarding associations between polymorphisms of the oxytocin receptor (OXTR) gene and socio-emotional and behavioral functioning in children and adolescents. The search yielded 69 articles, which were grouped into nine categories: depression, anxiety, and internalizing symptoms, alcohol abuse, borderline personality disorder, conduct disorder symptoms or diagnosis, autism spectrum disorder, attention deficit hyperactivity disorder, early childhood attachment and behavior, pro-social skills, and resilience. Direct and/or gene x environment interactions were identified in over half of the studies. ASD and conduct disorder (including callous unemotional traits) were the diagnoses that were most studied and for which there was the strongest evidence of direct links with OXTR polymorphisms. In most studies identifying gene x environment interactions, the candidate OXTR polymorphism was rs53576. Results suggest that OXTR polymorphisms are associated with social, emotional or behavioural functioning in children and adolescents. The mixed findings do, however, highlight the need for further research. Highlights: OXTR polymorphisms are associated with social/emotional/behavioral functioning in children and adolescents. The conditions for which OXTR SNPs appear to be most relevant are ASD and conduct problems. The specific polymorphism implicated most strongly in the prediction of social/emotional/behavioral functioning is OXTR rs53576.